Back in business: Industrial policy for emerging economies in the new globalization - Erik Berglöf; Vince Cable (Asian Development Bank (ADB), 2018)
We explore the potential roles of industrial policy in the transition from middle-income to high-income status, and the actual experience of industrial policy in emerging economies. Guided by the conceptual framework of the neo-Schumpeterian approach, we look at industrial policy in the context of structural transformation, i.e., in transforming economic structures as well as the institutions supporting these structures. Today's emerging economies face a dual structural transformation challenge: (i) to move closer to the current world technology frontier (traditional catch-up), and (ii) to adjust to technological change in advanced economies and increasingly binding environmental and social constraints. The feasible set of industrial policy is constrained by state capacity. The paradox of industrial policy is that it is most straightforward when state capacity is the most constrained. We suggest that emerging economies still should explore what we denote as sector-based horizontal policies addressing market and state failures in individual industries.
Keywords: F43; L52; O31; O38; O43; O47; 330; emerging economies; industrial policy; innovation; state capacity; structural transformation